Optimal Management of the Enterprise's Financial Flows - OLIINYK, Viktor (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
This article discusses the formulation and solution of some problems of managing the company's investment flows. One-product dynamic macroeconomic model is considered. When solving the problems posed, the Pontryagin maximization method is used. As a condition of optimization the criterion of maximization of the enterprise income is used. The optimal distribution of the gross product is given.